Governmental Policies to Fight Pandemic : The Boundaries of Legitimate Limitations on Fundamental Freedoms - Vedaschi, Arianna, (International Law E-Books Online, Collection 2025., 2024)
This book offers a wide comparative overview of the legal measures enacted by countries throughout the world to react to the unprecedented public health emergency caused by the COVID-19 pandemic. The volume gathers the General Reports and selected National Reports presented at the 2022 General Congress of the International Academy of Comparative Law. While the National Reports focus on single countries, the General Report provides a comparative analysis of observed trends and main legal issues. In doing so, it draws some guidelines on how to improve responses to potential forthcoming emergencies characterized by a global reach, as COVID-19 was. See Less